Klasifikasi Perbuatan Advokat Dalam Tindak Pidana Obstruction Of Justice Berdasarkan Ketentuan Hukum Pidana: Studi Kasus Putusan Nomor 3315 K/Pid.Sus/2018 - Mugiono Mugiono (Universitas Palangka Raya, 2024)
The existence of a code of professional ethics is very important in order to keep advocates in practice or law does not come out of the values of the profession. The code of ethics is also needed to maintain that advocates serve the interests of the community and maintain the trust that has been given by the community to the community. The purpose of this study to determine the classification of criminal acts obstruction of justice in Decision No. 3315 K/Pid.Sus/2018. The act of the defendant who contacted and met with Doctor Bimanesh Sutarjo to ask for help so that his client could be hospitalized at the Medika Permata Hijau hospital with a diagnosis of several diseases, one of which was hypertension